2017
DOI: 10.1002/ece3.2849
|View full text |Cite
|
Sign up to set email alerts
|

Elements of metacommunity structure in Amazonian Zygoptera among streams under different spatial scales and environmental conditions

Abstract: An important aspect of conservation is to understand the founding elements and characteristics of metacommunities in natural environments, and the consequences of anthropogenic disturbance on these patterns. In natural Amazonian environments, the interfluves of the major rivers play an important role in the formation of areas of endemism through the historical isolation of species and the speciation process. We evaluated elements of metacommunity structure for Zygoptera (Insecta: Odonata) sampled in 93 Amazoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 59 publications
(132 reference statements)
3
36
0
1
Order By: Relevance
“…Taken collectively, the above‐mentioned findings suggest that past historical events shaped taxon distribution in the way they shaped the distribution and physiographic features of the ecoregional types across the Orinoco basin (e.g., Goosen, ; van der Hammen, ; Hoorn et al, ; Hughes & Eastwood, ). Several studies have indicated that a concordance between species pools and ecoregion (or biogeographical region) distributions provides indirect evidence of the effects of historical events on present‐day biodiversity patterns (Brasil et al, ; Hazzi, Moreno, Ortiz‐Movliav, & Palacio, ; Presley & Willig, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken collectively, the above‐mentioned findings suggest that past historical events shaped taxon distribution in the way they shaped the distribution and physiographic features of the ecoregional types across the Orinoco basin (e.g., Goosen, ; van der Hammen, ; Hoorn et al, ; Hughes & Eastwood, ). Several studies have indicated that a concordance between species pools and ecoregion (or biogeographical region) distributions provides indirect evidence of the effects of historical events on present‐day biodiversity patterns (Brasil et al, ; Hazzi, Moreno, Ortiz‐Movliav, & Palacio, ; Presley & Willig, ).…”
Section: Discussionmentioning
confidence: 99%
“…As these ecoregional features do not always match the extension of the stream networks, this scenario provides the opportunity to test the influence of the potential occurrence of different pools of species metacommunity structure. The few comparable studies carried out in the Tropics have indicated the occurrence of several pools of species across the region (Benito et al, ; Brasil, Vieira, Oliveira‐Junior, Dias‐Silva, & Juen, ; Datry et al, ). However, to our knowledge only one has addressed how the occurrence of different pools of species may shape the structure of phytoplankton metacommunities (Benito et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat integrity summarises coverage of riparian forest, the land use adjacent to the riparian zone and some characteristics of the stream channel, such as bank structure of rivers (Hannaford et al ., ; Roy et al ., ; Nessimian et al ., ), and can be interpreted as forest cover (Nessimian et al ., ). Indeed, this variable is an important predictor of Zygoptera species richness and composition in Amazonia (Monteiro Júnior et al ., ; Oliveira‐Junior et al ., ; Brasil et al ., ) and other Brazilian biomes (De Marco et al ., ; Mendes et al ., ). With increasing forest cover, the dominance of damselfly species increases, while the dominance of dragonflies decreases (De Marco et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although commonly considered a homogeneous environment, Amazonia is in fact divided in distinct macroclimatic zones within the tropical climate, from superhumid in the western Amazon due to the strong influence of the Andes, to progressively subhumid in central Amazon, and even presenting dry winters at the southern and eastern Amazon basin (Peel et al ., ). These differences in macroclimatic patterns increase the regional species richness of Odonata by increasing the spatial turnover of species (Brasil et al ., ) that occupy distinct physiological niches (Collins & McIntyre, ; Amundrud et al ., ). Indeed, they explain the strong climatic effects on the species richness of the biogeographical modules, which are thought to capture the determinants of geographic species ranges.…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomic and phylogenetic diversity of some animal groups, such as primates and birds, is known to be strongly related to the formation and structure of these interfluves (Wallace, 1854;Ayres & Clutton-Brock, 1992;Ribas et al, 2012;Pomara et al, 2014). In the specific case of the Odonata, at large spatial scales, the distribution of species of the Zygoptera is closely related to areas of endemism (Brasil et al, 2017). This is because the Zygoptera have a reduced capacity for dispersal, making the major Amazonian rivers important geographical barriers to their dispersion, and thus over time, forming areas of endemism corresponding to the interfluves of these major rivers (Juen & De Marco, 2012).…”
Section: Introductionmentioning
confidence: 99%